The impact of time-limited context and feedback methods on epistemic curiosity - Guo, Zexi; Nadila, Yibulayin; Yilizhati, Maimaiti (Frontiers in Psychology, 2025)
In the school environment, students’ knowledge acquisition typically occurs within a limited-time context that includes external feedback. However, it remains unclear how such contexts influence students’ epistemic curiosity. This study examines the impact of external time limitation and different feedback methods on epistemic curiosity during the learning process through two studies. Study 1 compared epistemic curiosity between limited-time and no-time-limit conditions, finding that participants in the limited-time condition exhibited significantly higher epistemic curiosity. Study 2 investigated the effects of correctness feedback, score feedback, and ranking feedback on epistemic curiosity in a limited-time context, revealing that only correctness feedback significantly enhanced epistemic curiosity. This suggests that external time constraints in the knowledge learning process can stimulate epistemic curiosity, and correctness feedback can sustain this effect.